2004
DOI: 10.1143/jpsj.73.3149
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Doping Induced High-Spin in a Model of Polyene-based Molecular Magnets

Abstract: Control of intramolecular spin alignment is studied theoretically in a model of polyene-based molecular magnets in which delocalized π electrons are coupled with localized radical spins. In a previous paper [Phys. Rev. Lett. 90 (2003) 207203], we have demonstrated that charge doping is an effective way to realize controllable high-spin in the π-conjugated molecular magnets. In this paper, we clarify the dependence of spin-alignment on the exchange interaction between the localized spin and π electron and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…44 It has been demonstrated that high-spin states can be induced by hole-doping in the polyene-based molecules, 45 depending sensitively on the molecular structure and the system parameters. 46 More recently, we have conducted studies on the spin-alignment alteration upon hole-doping in more realistic molecules. 47 However, besides all these efforts, few theoretical investigations have been oriented to spin alignment in excited states related to photoinduced high spin.…”
Section: Introductionmentioning
confidence: 99%
“…44 It has been demonstrated that high-spin states can be induced by hole-doping in the polyene-based molecules, 45 depending sensitively on the molecular structure and the system parameters. 46 More recently, we have conducted studies on the spin-alignment alteration upon hole-doping in more realistic molecules. 47 However, besides all these efforts, few theoretical investigations have been oriented to spin alignment in excited states related to photoinduced high spin.…”
Section: Introductionmentioning
confidence: 99%